DRM para proteção de conteúdo de VOD utilizando o SGX: uma abordagem de avaliação de desempenho de descriptografia voltado para Set-Top Boxes - Costa, Ricardo de Souza (2019)
Video on Demand or simply VOD is a streaming media service that requires high bandwidth on IPTV networks, but it is also a huge source of revenue for content providers, broadcasters and infrastructure providers. Customers can select TV media contents from a large digital media library and are no longer dependent on an EPG (Electronic Program Guide). However, the VOD service must make streaming content chosen only for personalized customers, it means that the system must protect data transfer and storage in order to prevent copyright infringements or unfair business competition with illegally acquired content. With this issue in evidence, a DRM (Digital Rights Management) solution based on Intel SGX (Software Guard Extensions) technology is implemented, focusing on the client device, to evaluate video decryption performance in progressive scanning of 480, 720, 1080 and 2160 video resolutions into an enclave. The result shows the decryption performance of an 2160p video resolution, with an input data buffer of 32kB into the enclave, for example, gets an average of 10ms. Consequently, this result is compatible with the requirements of video decoder devices available on the market.